W sprawie programowania międzynarodowej specjalizacji produkcji - Guzek, Marian (Wydział Prawa i Administracji UAM, 1976)
The author points out that the research work being an object of W. Samowol's "Observations", was intended to bring practical solutions, therefore its task was to adjust theoretical conceptions to the actual economic conditions. The theoretical solutions themselves had been worked out and presented in other publications. They have not been, however, mentioned by W. Samowol. The author has not confirmed a reservation on uncomparability of the two variants, showing that the reservation was caused by an incorrect interpretation of the numerical elements of calculation.
On Programming International Specialization o f Production